Factors that influence environmental, social and governance (ESG) rating for public listed companies in FTSE4 good bursa saham Malaysia index (F4GBM Index) - Yasmin, Mohamad Tahir (2019)
The purpose of this study is to examine the factors that influence environmental, social and governance (ESG) rating for public listed companies in FTSE4 Good Bursa Malaysia Index (F4GBM Index). The analysis is based on the sample from 31 public listed companies in F4GBM Index as of June 2017. The sample period covered from 2007 to 2016. Using Generalized Method of Moments (GMM) and Pooled OLS Model (POLS), the results of this paper indicate that credit ratio and liquidity ratio have positive significant relationships with ESG rating, environmental rating and governance rating but profitability ratio and DuPont analysis ratio are not significant with ESG rating, environmental rating and governance rating. Meanwhile for social rating, it has positive significant with profitability ratio, credit ratio and liquidity ratio but not significant with DuPont analysis ratio for the 31 public listed companies in F4GBM Index. This research contributes to the literature based on the context of Malaysian public listed companies which are listed in F4GBM Index and delivers empirical evidence on the influences of profitability ratio, credit ratio, liquidity ratio and DuPont analysis ratio towards ESG rating. The findings of the study will be highly beneficial for securities capital market investors in making ESG investments in Malaysia's public listed companies through the disclosures made on financial performances of profitability ratio, credit ratio, liquidity ratio and DuPont analysis ratio. As for the public listed companies, it will help to boost up the profile and exposure of public listed companies which leading in ESG practices and to create an environment or encouragement for best practice disclosure by the public listed compames.